WORKING OF THE LOKAYUKTAS IN STATES- A CRITICAL ANALYSIS - Parishkar Shreshth (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The Lokayukta is an anti-corruption watchdog. A Lokayukta cannot be revoked or transferred by the government, and must only be withdrawn by an impeachment motion by the assembly. Naresh Kadyan battled to have a Lokayukta set up in Haryana. The group of officials led by Morarji Desai submitted a study on "Problems of Redressal of Citizen’s Grievances" in 1966. In this report, the ARC proposed that two bodies be set up named "Lokpal" and "Lokayukta" which would be known as the chief security officers to guard the interests of common man and to prevent corruptions. Lokayukta is considered to be an incorruptibility of government. Not least it investigates the charges of wrongdoing and arrogance towards public servants and is responsible for speedy redress of grievances. This paper will examine critically the workings and schemes in various Indian states.